Konsep Kesempurnaan Hidup Orang Jawa: Sebuah Tinjauan Filologi Terhadap Serat Madurasa - Muhammad Safii (Jumantara: Jurnal Manuskrip Nusantara, 2021)
Serat Madurasa manuscript contains moral guidelines, life instructions for humans, advice for individuals in dealing with God, as well as social relationships and personal self, especially for Kawruh Hardapusara followers. This Manuscript is the work of R. Sujanareja who is a member of Penghayat Kawruh Hardapusara, as well as Ki Kusumawicitra's favorite student. Penghayat Kawruh Hardapusara was initiated by Ki Kusumawicitra from Purworejo. The purpose of this study is to present the results of the text edition so that the manuscript can be read and understood by a wide audience, and to analyze the contents of the manuscript. This study uses a philological study approach. From this research, it can be seen that the efforts of the members of Penghayat Kawruh Hardapusara in achieving the perfection of life are based on the Serat Madurasa.